Nutrient driven transcriptional changes during phage infection in an aquatic Gammaproteobacterium. (26th January 2022) - Nilsson, Emelie; Li, Ke; Hoetzinger, Matthias; Holmfeldt, Karin
Summary: Phages modulate bacterial metabolism during infection by regulating gene expression, which influences aquatic nutrient cycling. However, the effects of shifting nutrient regimes are less understood. Here, we analyzed transcriptomes of an ecologically relevant Gammaproteobacterium and its lytic phage in high (HNM) and low (LNM) nutrient medium. Despite different infection characteristics, including reduced burst size and longer latent period in LNM, the phage had a fixed expression profile. Bacterial transcription was instead different depending on nutrient regime, with HNM bacteria focusing on growth while LNM bacteria focused on motility and membrane transport. Additionally, phage infection had a larger effect on bacterial gene expression in LNM compared to HNM, e.g. suppressing increased iron uptake and altering expression of phosphorus uptake genes. Overall, phage infection influenced host metabolism more in LNM, which was more similar to natural conditions, emphasizing the importance of considering natural conditions to understand phage and host ecology.